Applied scope of practice of oral health therapists, dental hygienists and dental therapists. (September 2016) - Teusner, DN; Amarasena, N; Satur, J; Chrisopoulos, S; Brennan, DS
Abstract: Background: Oral health therapists (OHTs) are an emerging workforce whose training incorporates the skills of dental hygienists (DHs) and dental therapists (DTs). There are concerns that OHTs are underutilized. This study compares the employment characteristics and applied practice scope of OHTs with those of DTs and DHs. Methods: Members of two professional associations representing DHs, DTs and OHTs, were surveyed by mail. Data collected included demographic and employment characteristics and clinical activity on a typical practice day. Applied practice scope was described by calculating the proportion of practitioners that had provided ≥1 of a selected range of key services. Log binomial regression was used to compare OHTs to DTs and DHs. Results: The response rate was 60.6% (n = 1083) and of these 90.9% were employed. Preventive services dominated service provision. The proportion of OHTs that provided fluoride applications (77%) was higher than the proportion of DTs (53%, p < 0.05), and was not significantly different from the proportion of DHs (70%). The proportion of OHTs that provided (48%) fissure sealants was lower than the proportion of DTs (70%) and substantially higher than the proportion of DHs (10%, p > 0.05). Conclusions: Overall, the applied practice scope of OHTs appeared to differ from DTs and DHs.